Manga, graphic novels, and comics in Higher Education? - Hendrik van der Sluis (New Vistas, 2021)
Particularly known for playing a key role in the daily entertainment of millions of people worldwide, this article explores the relevance of manga, graphic novels, and comics to diversify curricula and making learning more engaging, and explores why this is of value for Higher Education.